Negotiating Interior Frontiers: Lara Haddad’s A Question of History (2015–16) - Golańska, Dorota (Text Matters: A Journal of Literature, Theory and Culture, 2023)
Bringing together insights originating in law studies and art analysis, this article approaches the work of the US-based Syrian artist Lara Haddad through the figuration of “interior frontiers,” exposing how both “interior bonds” and “internal borders” tended to shape legal regulations introduced in the US in the aftermath of 9/11 for the purpose of conducting “the global war on terror.” Referring to the concept of “plasticity,” the article examines the intimate (dis)identifications experienced by the artist in the context of the politically saturated cultural discourses on violence which emerged from the post-9/11 spatialities of (inter)national law. The article argues that politically engaged art offers a means to affectively connect with the personal ways of coping with the persistent visceral presence of structural violence, shedding light on how political protocols and cultural representations impinge upon the individual experiences of many Muslims residing inside and outside the US territory. Opening established meanings to new interpretations, such art contributes to the process of revising dominant oppressive significations, creating room for critical contestation and increased transcultural understanding.